2006
DOI: 10.1371/journal.pbio.0040226
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones Stimulate Arbuscular Mycorrhizal Fungi by Activating Mitochondria

Abstract: The association of arbuscular mycorrhizal (AM) fungi with plant roots is the oldest and ecologically most important symbiotic relationship between higher plants and microorganisms, yet the mechanism by which these fungi detect the presence of a plant host is poorly understood. Previous studies have shown that roots secrete a branching factor (BF) that strongly stimulates branching of hyphae during germination of the spores of AM fungi. In the BF of Lotus, a strigolactone was found to be the active molecule. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
428
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 721 publications
(468 citation statements)
references
References 41 publications
11
428
2
1
Order By: Relevance
“…In agreement with previous observations (Besserer et al, 2006), the 3-h treatment with GR24 increased the transcription of genes encoding NADH Dehydrogenase and COX 1 in both the lines (Supplementary Figure S8), with a significantly higher fold-change ratio in the B+ line for COX1 (Figure 7). By contrast, the results were less clear-cut when ROS-related genes were considered: only the transcript of glutathione peroxidase, which uses H 2 O 2 as a substrate, was strongly upregulated in the B+ spore, when compared with the cured line.…”
Section: Endobacterial Impact On the Am Fungus Fitnesssupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous observations (Besserer et al, 2006), the 3-h treatment with GR24 increased the transcription of genes encoding NADH Dehydrogenase and COX 1 in both the lines (Supplementary Figure S8), with a significantly higher fold-change ratio in the B+ line for COX1 (Figure 7). By contrast, the results were less clear-cut when ROS-related genes were considered: only the transcript of glutathione peroxidase, which uses H 2 O 2 as a substrate, was strongly upregulated in the B+ spore, when compared with the cured line.…”
Section: Endobacterial Impact On the Am Fungus Fitnesssupporting
confidence: 92%
“…SLs stimulate mitochondrial activity in the germinating spores of the AMF Gigaspora rosea, which does not contain endobacteria (Besserer et al, 2006). Our analysis surprisingly reveals that the endobacterium and the SL treatment lead to a similar transcriptomic response under the tested conditions (7 days after germination), that is, upregulation of the genes encoding NADH dehydrogenase and Cytochrome oxidase I (COX 1) in the fungus.…”
Section: Endobacterial Impact On the Am Fungus Fitness A Salvioli Et Almentioning
confidence: 61%
See 1 more Smart Citation
“…This involvement makes VP14 an attractive target for the development of novel chemical agents and genetic modifications to control ABA levels and improve plant productivity, performance, and architecture (Cutler and Krochko, 1999;Qin and Zeevaart, 1999) (Figure 1). Studies of the mutant vp14-2274 also implicate VP14 in the synthesis of strigolactones (Matusova et al, 2005), signaling molecules involved in shoot branching (Gomez-Roldan et al, 2008;Umehara et al, 2008), presymbiotic growth of arbuscular mycorrhizal fungi (Besserer et al, 2006), and parasitic weed germination (Hauck et al, 1992;Siame et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This enhancement of oxydative metabolism precedes active mitochondrial proliferation. 6,7 Taken together, these results suggested that mitochondrial activation is a key event required for switching the fungus to a pre-symbiotic stage, characterized by a more active nuclear proliferation, an upregulation of several genes and an activated cell proliferation (the so called branching response). 6 In order to clarify the role of mitochondria in the GR24 response, we carried out a series of pharmacological experiments where different steps of the oxidative phosphorylation were specifically inhibited.…”
mentioning
confidence: 85%